Konseling Perdamaian dalam Konteks Peribahasa dan Saloka Jawa: The Peace Conseling Based on Saloka - Taufiqurrahman; Zayadi, Ahmad; Hara, Hara Permana (Direktorat Jenderal Bimbingan Masyarakat Islam, 2024)
The purpose of this study is to explore the values of peace contained in Javanese saloka, with a special focus on internalizing saloka values into peace guidance. This research is a research with a qualitative descriptive approach. The data in the study was divided into primary, secondary, and tertiary data. The primary data in this study are Javanese poetry and proverb textbooks by and Javanese expression meanings books by. Based on the results of data analysis, there are several saloka that uphold the principles of harmony, respect, and peace, namely saloka jembar segarane, menang tanpa ngasorake, Crah Agawe Bubrah Rukun Agawe Santosa, and Tepo Seliro. Peace guidance based on local wisdom can be done classically or in groups by adopting peace education procedures which include rational stages of the peace counseling model, exploring the root causes of violence and aggression, reflecting on the phenomenon of violence from a cultural perspective, teaching peace values contained in Javanese proverbs and saloka as alternative problem solving, looking for different forms of violence and eliminate them, and evaluate and follow up peaceful thoughts, feelings, and behaviors. Counselors can train individuals to behave peacefully in both verbal and nonverbal forms. When a person can practice peaceful behavior, then they can suppress aspects of aggressiveness, which include physical, verbal, anger, and hatred.